THE IMPINGEMENT OF AUDIT TENURE, AUDIT FEES, ABILITY AND AUDITOR’S INDEPENDENCE REGARDING AUDIT QUALITY - Siboro, Theresia Citra; Ruslim, Herman (JURNAL ILMIAH EDUNOMIKA, 2024)
Prevalent global economic competition has become increasingly fierce, both in business sectors and service industries such as Public Accountant Firm (KAP). With the growth of businesses that are listed on the Indonesia Stock Market, there is a rising demand for high-quality audit reports. Therefore, auditors must continually enhance the quality of their audits. This research looks into the effects of audit tenure, audit fees, ability, as well as auditor’s independence regarding audit quality. Primary data for this study were obtained through the distribution of questionnaires via Google Forms to the auditors in Public Accountant Firm (KAP) in the DKI Jakarta region. The research employed 45 sample size for purposive sampling. It made use of multiple linear regression in the analysis to examine information, and outcomes showed the proficiency variable significantly affects audit quality. However, audit tenure, audit fees, and auditor independence do not significantly affect audit quality.